Mid‐term effects on sinus node function following additional empirical superior vena cava isolation in atrial fibrillation patients with sick sinus syndrome - Miwa Kanai; Satoshi Higuchi; Masayuki Sakai; Yuko Matsui; Shun Hasegawa; Daigo Yagishita; Morio Shoda; Junichi Yamaguchi (Journal of Arrhythmia)
Abstract Aim The safety of including superior vena cava isolation (SVCI) along with pulmonary vein isolation (PVI) in atrial fibrillation (AF) patients with sick sinus syndrome (SSS) remains uncertain, as this decision is often left to the discretion of individual physicians. Methods and Results In this retrospective study, 94 AF patients with SSS, who underwent PVI without prior pacemaker placement, were divided into two groups: those with (n = 67, age 66.0 ± 9.3 years, male 61%) and without (n = 27, age 66.6 ± 10.0 years, male 63%) additional empirical SVCI. SVCI was performed at 25–35 W, 10–20 mm superior to the earliest sites of activation during sinus rhythm. The primary endpoint compared atrial tachyarrhythmia (ATA) recurrence, pacemaker avoidance, and 24‐hour ambulatory monitoring results between the SVCI and non‐SVCI groups. Preprocedure minimum heart rate (SVCI 37.6 ± 11.6 Bpm vs. non‐SVCI 37.0 ± 9.9 Bpm, p = 0.74) and maximum pause (SVCI 4.2 ± 2.7 Sec vs. non‐SVCI 3.6 ± 2.8 Sec, p = 0.15) were not different between the two groups. During 36 months of follow‐up after the last procedure, ATA recurrence rates (SVCI 33% vs. non‐SVCI 34%, p = 0.82) and pacemaker avoidance rates (SVCI 84% vs. non‐SVCI 93%, p = 0.32) Were Comparable between the two groups. At 36 months after the last procedure, minimum heart rate (SVCI 48.7 ± 10.2 bpm vs. non‐SVCI 47.4 ± 8.3 bpm, p = 0.52) and maximum pause (SVCI 1.6 ± 1.0 sec vs. non‐SVCI 1.6 ± 0.6 sec, p = 0.33) remained similar between the two groups. Conclusion In this study, the addition of SVCI did not significantly increase the need for pacemaker implantation or lead to sinus node dysfunction in AF patients with SSS compared to PVI alone.